MODERN TRENDS IN ENVIRONMENTAL ACTIVITIES OF TRANSNATIONAL CORPORATIONS - E. Tolokonnikova (Вестник университета)
The article discusses some of the modern trends in environmental activities of multinational corporations and gives a brief description of each. The article summarizes the new material on the subject studied and indicated the importance of each direction for transnational corporations.